From the ground up: Demining farmland and improving access to fertilizer to restore Ukraine’s agricultural production - Welsh, Caitlin; Dodd, Emma; Dankevych, Vitalii; Glauber, Joseph W.; Broyaka, Antonina (Center for Strategic and International Studies, 2023)
In the two decades leading up to Russia’s February 2022 invasion, Ukraine had become a major producer and exporter of numerous agricultural commodities. In the 2020–2021 harvest season—the last season unaffected by Russia’s full-scale invasion—Ukraine was the fifth-largest exporter of wheat, honey, and walnuts worldwide; the third-largest exporter of maize, barley, and rapeseed; and the world’s top exporter of sunflower oil, sunflower meal, and millet.